ANALISIS KUALITAS PELAYANAN KEPADA KEPUASAN PELANGGAN JASA PENGINAPAN (STUDI EMPIRIS DI HOTEL LOR IN SOLO) - NUGROHO, YAN TOTO (2011)
Companies always theirs business activities in order to provide the best value for the growth and safety of the company. In addition, consumers are also very important to the success of a service sector company. Each company have to develop some strategies to attract consumers attention for becoming for a satisfied customer. The purpose of this research are (1) to analyze the differences between the perceived quality of customer service with the expected quality of customer service based on inn services, (2) to analyze the influences of service quality dimensions including reliability, responsiveness, confidence, and tangible emphaty to customer satisfaction inn services, (3) to analyze the dimensions of service quality of the most dominant influence on customer satisfaction of service users at Hotel Lor in Solo. The location of the research is Hotel Lor In Solo. The population of this research is that all consumers at Hotel Lor In during the year 2010 as many as 40,974 or an average of as many as 3414 people per month customer. The samples in this study were taken as many as 100 people subscribers and sampling technique used was accidental sampling. Data collected by a questionnaire about the quality of service and customer satisfaction. Data were analyzed using multiple regression techniques and mean analyzed gap. The results showed that: (1) There is a difference and significant between the average quality of service expected by the average customer perceived service quality Hotel Lor In Sol, (2) Tangible variables have an influence on customer satisfaction significant at 0,002 < 0,05 , (3) reliability variables have an influence to customer satisfaction significant at 0,002 < 0,05, (4) Variable responsiveness have an influence on customer satisfaction significant at 0,001 < 0,05, (5) Variable confidence have an influence on customer satisfaction significant at 0,030 < 0,05, (6) emphaty variables have an influence on customer satisfaction significant at 0,007 < 0,05.